PERANCANGAN PROTOTYPE ILUSTRASI DAN PACKAGING MUG CAKE “MINUTESBAKE” - Levina, Lulu; Sutanto, Shienny Megawati (Jurnal VICIDI, 2020)
Nowadays, Surabaya is famous with new inventions created in cullinary world. Therefore, people are starting to be insterested learning cooking or baking on their own. However, baking requires steps that are not easy. Minutesbake is a business focusing on culinary product, especially cakes. Unlike cakes in general, Minutesbake it’s an instant baking mix that only use microwave and cooked in a mug. The purpose of this research is to find out the amount of interests towards Minutesbake, as well as to learn target market’s needs and wants. The research method that will used are through quantitative and qualitative method.